Research progress on the regulation and mechanism of osteocytes on osteoblasts and osteoclasts - YANG Zhenming; ZHANG Shuyu; QIANG Jinbiao; SHI Yan; WANG Xiaoling; SHI Ce (Kouqiang hemian waike zazhi)
With the continuous explorations and researches of osteocytes, osteocytes are no longer mistaken for a kind of quiescent and passive cells, but active and positive cells, which play important regulatory roles in osteoblasts and osteoclasts. While an increasing number of studies have identified key signaling pathways and crosstalk mechanisms related to osteocytes. To some extent, the role of osteocyte apoptosis and its complex mechanisms occurring in various states of pathologies are still not elucidated. If further studies can be performed, this will help to fully understand the function and mechanism of osteocytes in a variety of states, as well as provide a novel target for bone diseases. At present, there are many reports about osteocytes regulating osteoblasts and osteoclasts. In this paper, the research progresses in regulation and mechanism of osteoblasts and osteoclasts by osteocytes are reviewed.